Universal varicella vaccine immunization in Japan. Issue 16 (7th April 2016) - Yoshikawa, Tetsushi; Kawamura, Yoshiki; Ohashi, Masahiro
Abstract: In 1974, Japanese scientists developed a live attenuated varicella vaccine based on the Oka strain. The efficacy of the vaccine for the prevention of varicella has been primarily demonstrated in studies conducted in the United States following the adoption of universal immunization using the Oka strain varicella vaccine in 1996. Although the vaccine was developed by Japanese scientists, until recently, the vaccine has been administered on a voluntary basis in Japan resulting in a vaccine coverage rate of approximately 40%. Therefore, Japan initiated universal immunization using the Oka strain varicella vaccine in November 2014. Given the transition from voluntary to universal immunization in Japan, it will also be important to monitor the epidemiology of varicella and herpes zoster. The efficacy and safety of co-administration of the varicella vaccine and measles, mumps, and rubella vaccine have been demonstrated in many countries; however, there was no data from Japan. In order to adopt the practice of universal immunization using the Oka strain varicella vaccine in Japan, data demonstrating the efficacy and safety of co-administration of varicella vaccine and measles and rubella (MR) vaccine were required. Additionally, we needed to elucidate the appropriate time interval between the first and second administrations of the vaccine. It is also important to differentiate between wild type and Oka vaccine type strains in herpes zoster patient with past history of varicella vaccine. Thus, there are many factors to consider regarding the adoption of universal immunization in Japan to control varicella zoster virus (VZV) infections.